Pengaruh Lingkungan Sekolah terhadap Pembentukan Karakter Siswa Sekolah Dasar - Irma Sari Daulay; Seprina Hasibuan; Salimah Intan Daulay; Parlindungan Nasution; Ika Pitriani Lubis; Fazriani Hasibuan; Nadia Khoirunnisa Dly (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Character education is a fundamental aspect in shaping the personality of elementary school students, whose development is greatly influenced by the school environment. A conducive school environment, including values, norms, school climate, and teacher role models, plays an important role in instilling positive character in students from an early age. This study aims to determine the influence of the school environment on the character formation of elementary school students at SDN 0107 Tanjung Botung. The research method used is quantitative research with a descriptive analysis approach. The research population consisted of 289 students with a sample of 47 students selected using random sampling techniques. Data collection techniques were carried out through observation, questionnaires, and documentation, while data analysis used descriptive statistics and simple linear regression with the help of the SPSS program. The results showed that the school environment had a significant effect on the character formation of students, as evidenced by a significance value of 0.001 < 0.05 and a t-value greater than the t-table. The coefficient of determination shows that the school environment contributes 21% to the formation of student character. The conclusion of this study confirms that the better the school environment, the more optimal the formation of student character, so that continuous efforts from the entire school community and support from families and the community are needed to strengthen character education.